A numerical investigation of injury mechanisms and tolerance limit of occupant femur in combined compression–bending load. Issue 2 (4th March 2022) - Wang, Bingyu; Yu, Chao; Jiang, Xiaoqing; Peng, Qian; Zhang, Yi; Wang, Fang
Abstract: This study aimed at investigating the femur injury mechanisms and femur injury tolerance limit in combined axial force and bending moment. A finite element (FE) model of the lower extremity in sitting posture was developed and validated against femur three-point bending dynamic test and axial impact test of knee-thigh (KT) complex. Following, the femur fractures in combined compression–bending load were analysed via using an analytical model of the curved beam. At last, six virtual simulation tests were conducted by using the developed femur FE model. Moreover, the femur fracture mechanism was analysed in terms of the fracture location and the calculated failure bending moments from both the analytical and FE models. The results revealed that with the increasing of preload bending moment from 0 to 676 Nm, the femur fracture location transferred from the femoral neck region to the femoral shaft region. In the two simulation tests of femur fractures in femoral neck regions, the peak value of femur bending moment were 285 and 296 Nm, respectively. In the other four tests with femur fractures occurred in shaft region, the fracture femur moment varied from 381 to 443 Nm. The results demonstrated that the occupant femur fracture location and femur fracture tolerance limit were affected by both bending moment and axial compression loads. This study can provides an explanation for the phenomenon that the high prevalence of femoral shaft fractures occurs in real-world car frontal impacts when the axial loads lower than that used in the current injury tolerance of femur.